Dispositional Explanations of Behavior. - Vanderbeeken, Robrecht; Weber, Erik (Behavior and Philosophy, 2002)
If dispositions are conceived as properties of systems that refer to possiblecausal relations, dispositions can be used in singular causal explanations. By means of these dispositional explanations, we can explain behavior B of a system x by (i) referring toa situation of type S that triggered B, given that x has a disposition D to do B in S, or (ii) byreferring to a disposition D of x to do B in S, given that x is in a situation of type S.Dispositional explanations are adequate and indispensable explanations: they can explain behavior B without explicitly referring to the underlying causal basis in x that constitutes adisposition to do B. Radical Behaviorist explanations are a sort of dispositionalexplanations, but the dispositional model is not restricted to these explanations. Thedispositional model is compatible with, or can be applied to, several research programs